A novel variant in the SPTB gene underlying hereditary spherocytosis and a literature review of previous variants - Yang Wang; Tao Liu; Chenxi Jia; Li Xiao; Wen Wang; Yongjie Zhang; Yan Xiang; Lan Huang; Jie Yu (BMC, 2024)
Abstract Background Hereditary spherocytosis (HS, MIM#612641) is one of the most common hereditary hemolytic disorders. This study aimed to confirm a novel variant's pathogenicity and reveal a patient's genetic etiology. Methods The clinical data of a patient with HS who underwent genetic sequencing at the Children's Hospital of Chongqing Medical University were reviewed retrospectively. In silico prediction and in vitro minigene splicing reporter system were then conducted on the detected variant to analyze its intramolecular impact. A summary of the literature related to HS due to SPTB gene variants was also presented. Results A novel variant (c.301-2 A > G) in the SPTB gene (NM_001024858.4) was identified in the proband. Using Sanger sequencing, we conclusively confirmed that the inheritance of the variant could not be traced to the biological parents. The in vitro minigene assay revealed three different transcripts derived from the c.301-2 A > G variant: r.301_474del, r.301_306delCCAAAG, and r.301-1_301-57ins. Through a literature review, patients with HS who had been genotypically validated were summarized and the SPTB gene variant profile was mapped. Conclusion We identified a splicing variant of the SPTB gene, thus confirming its aberrant translation. The novel variant was the probable genetic etiology of the proband with HS. Our findings expanded the variant spectrum of the SPTB gene, thus improving the understanding of the associated hereditary hemolytic disorders from a clinical and molecular perspective and contributing to the foundation of genetic counseling and diagnosis.